Mengatasi Hedonisme Di Kalangan Generasi Z Melalui Konsep Zuhud Al-Ghazali - Azka, Naufal; Subekti, Fiqi Restu (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2025)
The phenomenon of hedonism has been observed to engender a state of spiritual emptiness among Generation Z. However, this condition can be overcome through a spiritual approach, one of which is zuhud. The present study aims to identify the forms of hedonism among Generation Z and to explore the potential of zuhud as a solution to this problem. The present study employs a qualitative methodology, underpinned by a comprehensive literature review. The data sources for this study were drawn from various relevant literature sources, including books, journal articles, social media news, and other information sources. The results of the study indicate that Generation Z tends to consume luxury goods, engage in expensive treatments, and spend money to enhance digital experiences, such as online games and streaming platforms. Al-Ghazali’s concept of zuhd emphasises a balance between worldly and spiritual needs. The term zuhd is not to be equated with the idea of complete worldly withdrawal, but rather denotes the application of judicious worldly practices in conjunction with spiritual anchoring to Allah. The study’s findings suggest that the implementation of the zuhd concept can assist Generation Z in re-establishing spiritual values, thereby facilitating a more harmonious balance between worldly and afterlife concerns.